If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-n+4(1+5n)=-6n-14
We move all terms to the left:
8-n+4(1+5n)-(-6n-14)=0
We add all the numbers together, and all the variables
-n+4(5n+1)-(-6n-14)+8=0
We add all the numbers together, and all the variables
-1n+4(5n+1)-(-6n-14)+8=0
We multiply parentheses
-1n+20n-(-6n-14)+4+8=0
We get rid of parentheses
-1n+20n+6n+14+4+8=0
We add all the numbers together, and all the variables
25n+26=0
We move all terms containing n to the left, all other terms to the right
25n=-26
n=-26/25
n=-1+1/25
| (4z/−16)=-2 | | 2w−5=5 | | 6=4+2n | | -8=2x-5x | | w-1/4=1/4 | | 4.3+x=7.6 | | -4(v-3)=-2v-4 | | 04(5x-2)=2(9x+3 | | v3+v4=56 | | 14+5=3x | | 2x+x+2x=540 | | x=1.5(-4) | | 8=4s=s+13 | | 10x-4(7x+1-(-88)+6=0 | | -5(p+53)=-4 | | -3r+4=-20 | | 28x-(8x-7)=67 | | -3(t+5)+(4t+42)=8 | | -3(t+5)+42=8 | | 2x-6=6x-54 | | 11(m+7)=99 | | 7x^2+36x+1=−4 | | x+96=96+x | | 8(z-6)=72 | | a,a=0 | | 11(m=7)=99 | | 30t+-5t2=9 | | 10=2/3m-2 | | 5n-8=-33 | | 9x^2=+6x+8=0 | | n/2-17=27 | | 5n-2n+3=2n-4n-2 |